Factors influencing the adoption of Instagram as a social commerce channel by SA consumers. - Girdharilall, Michelle (University of the Witswatersrand, Johannesburg, 2023)
The increasing popularity of social media has led to the rise of social commerce in South Africa. Consumers are welcoming these new modes of shopping as they offer more convenience than traditional electronic commerce methods. This research will seek to identify the factors which influence consumers to use Instagram social commerce. These insights are key to small businesses to attract and retain consumers on Instagram. This research is composed of fifteen qualitative interviews with purposely selected participants who have had experience using Instagram social commerce. The effect of Experience Quality, Perceived Easiness, Social Influence and Privacy Concerns were explored on consumers' trust and use of Instagram social commerce. Trust theory, Trust theory for social commerce and the Theory of Planned Behavior were used as foundations for this research. The results revealed that Experience Quality, Perceived Easiness, Social Influence and Privacy Concerns affected consumers' trust in Instagram social commerce. This research allowed us to probe into the details around these factors and identify relevant recommendations for businesses to succeed with Instagram social commerce.
A research proposal submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business
Keywords: Social commerce (S-commerce); eCommerce; Instagram; Social media; Theory of planned behavior; Online shopping; UCTD; SDG-9: Industry, innovation and infrastructure